RESPONS BEBERAPA VARIETAS PADI TERHADAP WAKTU PEMBERIAN BAHAN ORGANIK PADA METODE SRI - Muhammad Hatta (Jurnal Floratek, 2010)
The objective of study was to determine response of three varieties of rice to timing of providing organic fertilizer on SRI system. The results showed that the timing of providing organic materials exerted a significant effect on grain weight per hill and production per hectare, but no significant effect on variables of other rice growth and production. Provision of organic matter at planting date and a week after planting date gave  better grain weight per hill and production per hectare than a week before planting date. These results were consistent for all the tested rice varieties, i.e. Ciherang, Pandan Wangi, and Angke.  However, to some extent, Pandan Wangi was the best.